METTL3 Promotes the Resistance of Glioma to Temozolomide via Increasing MGMT and ANPG in a m6A Dependent Manner - Shi, Jia; Chen, Gang; Dong, Xuchen; Li, Haoran; Li, Suwen; Cheng, Shan; Li, Yongdong; Wang, Liping; Yuan, Jiaqi; Qian, Zhiyuan; Dong, Jun (Frontiers in Oncology, 2021)
Acquired chemoresistance is a major limiting factor in the clinical treatment of glioblastoma (GBM). However, the mechanism by which GBM acquires therapeutic resistance remains unclear. Here, we aimed to investigate whether METTL3-mediated N6-methyladenosine (m6A) modification contributes to the temozolomide (TMZ) resistance in GBM. We demonstrated that METTL3 METTL3-mediated m6A modification were significantly elevated in TMZ-resistant GBM cells. Functionally, METTL3 overexpression impaired the TMZ-sensitivity of GBM cells. In contrast, METTL3 silencing or DAA-mediated total methylation inhibition improved the sensitivity of TMZ-resistant GBM cells to TMZ in vitro and in vivo. Furthermore, we found that two critical DNA repair genes (MGMT and APNG) were m6A-modified by METTL3, whereas inhibited by METTL3 silencing or DAA-mediated total methylation inhibition, which is crucial for METTL3-improved TMZ resistance in GBM cells. Collectively, METTL3 acts as a critical promoter of TMZ resistance in glioma and extends the current understanding of m6A related signaling, thereby providing new insights into the field of glioma treatment.